Gambaran Cinta Pada Dewasa Awal Korban Perceraian Orang Tua - Novenia, Santa; Yuwono, Emmanuel Satyo (Universitas Trunojoyo Madura, 2024)
Divorce is a legal or religious separation between husband and wife. Divorce in the family has an impact on all family members. Children who are victims of their parents’ divorce experience psychological problems in their lives, so that when they grow up, these problems contribute to depicting romantic love relationships with other people. The aim of this research is to find out more deeply about the description of love in early adult victims of parental divorce. This research uses qualitative phenomenological methods on three early adult participants who were victims of parental divorce. The place where this research was conducted was Salatiga City, and Banyubiru Regency. Data were obtained through interview and observation techniques. The results of this study indicate that there is a fear of establishing closeness in love, low self-confidence in making a commitment, and giving effort to maintain a relationship. Based on this, expected that readers will have the awareness to create a positive love relationship.